Effects of exercise training during infusion on late-onset Pompe disease patients receiving enzyme replacement therapy. - Terzis, Gerasimos; Krase, Argyro; Papadimas, Giorgos; Papadopoulos, Constantinos; Kavouras, Stavros A; Manta, Panagiota (Mol Genet Metab, 2012)
Pompe disease is an autosomal recessive disorder caused by the deficiency of acid α-glucosidase resulting in lysosomal accumulation of glycogen and abnormal autophagic function. The late-onset form of the disease is characterized by progressive skeletal and respiratory muscle dysfunction. Enzyme replacement therapy (ERT, Genzyme Corporation, Cambridge, MA, USA) was recently introduced and resulted in significant prolongation of the life expectancy of the patients with the infantile form while the results were less significant for the late-onset form. It has been postulated that the weak influence of ERT in late-onset patients might be due to a non-effective delivery of the recombinant enzyme to the skeletal muscles perhaps due to the relatively low blood flow to the resting skeletal muscles during infusion. Exercise training acutely increases the blood flow to the exercising muscles. Thus, it was hypothesized that exercise training during enzyme infusion might increase the effectiveness of the ERT therapy. Five late-onset Pompe disease patients receiving ERT and following regular exercise training for approximately 10 months, followed a 6-month period of exercise training during infusion of the recombinant enzyme. Before and after this period, body composition, isometric strength and 6 minute walking distance were determined. Analysis of the results revealed that none of these parameters changed significantly after the 6-month intervention period (e.g. 6 minute walking distance before: 532±31 m, vs. after: 527±29 m, P=0.246). These results suggest that exercise training during infusion may not add significant functional changes in late-onset Pompe patients receiving ERT and undergoing regular exercise training.
Keywords: Adult; Age of Onset; alpha-Glucosidases; Body Composition; Enzyme Replacement Therapy; Exercise; Female; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Muscle Strength